IMPLEMENTASI KEPUTUSAN GUBERNUR KEPALA DAERAH TINGKAT I BALI NOMOR 394 TAHUN 1997 DALAM MEMBERIKAN PERLINDUNGAN HUKUM BAGI SEKAA/ ORGANISASI KESENIAN - BADRA, I MADE (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 1 No 1 (2012)DO - 10.24843/JMHU.2012.v01.i01.p03, 2012)
In order to create order and legal certainty to the type and quality of local arts to tourism, the Government of Bali Province issued the Regional Decision of The Governor of The Head of Bali Number 394 of 1997 on Regulating Regional Arts on The Province of Bali. Implementation of the Regional Decision of The Governor of The Head of Bali Number 394 of 1997 on Regulating Regional Arts on The Province of Bali of the terms, procedures and sanctions do not work effectively. These are caused because of legal substance, legal structure, legal culture and the means and facilities. To optimize the decision made by the Governor of the preventive and repressive efforts. To streamline the implementation of the Regional Decision of The Governor of The Head of Bali Number 394 of 1997 will require a synergy between the Department of Culture, sekaa / arts organizations and the service users. Regional Decision of The Governor of The Head of Bali Number 394 of 1997 should have to be amended because it does not fit with the times. Bali Provincial Cultural Office should be more proactive in doing preventive and repressive efforts in upholding the Regional Decision of The Governor of The Head of Bali Number 394 of 1997.
Keywords: Decision of the Governor, the arts and sekaa.